Produção e caracterização de carvão ativado modificado por sonicação e sua aplicação na adsorção de fármacos - Fröhlich, Andressa Cristiana (2019)
Water pollution by emerging contaminants such as pharmaceuticals has gained interest in recent years. These drugs have great potential in generating adverse effects for human and wildlife, since they are endocrine disruptors, bioaccumulative and potentially toxic. The release of pharmaceuticals into the water bodies occurs mainly through wastewater treatment plants because of their incomplete or inefficient removal during the conventional treatment process. Among them, ibuprofen and ketoprofen are common drugs used as pain relief. This work aimed to investigate the adsorption of these drugs by the use of standard activated carbon (SAC) and ultrasound modified activated carbon (UMAC) as adsorbent materials. The adsorbents were characterized in detail by Fourier transform infrared spectroscopy (FT–IR), X–ray diffraction (XRD), N2 adsorption isotherms (BET), helium gas picnometry, point of zero charge and scanning electron microscopy (SEM). The adsorption study was performed through the evaluation of pH effect (ranging from 2 to 10), contact time (ranging from 0 to 300 min), temperature (ranging from 25 to 55 °C) and estimation of thermodynamic parameters. Through the obtained data, adjustments to kinetic and isotherm models for both adsorbents were performed. In addition, a three–dimensional mass transfer model (PVSDM 3D) was applied to elucidate the adsorption of ibuprofen in both materials. Finally, a simulated effluent containing the contaminants under study was treated with SAC and UMAC. The results showed that UMAC presented better characteristics in comparison to SAC, such as higher surface area values, average pore diameter, pore volume and void fraction. The adsorption capacities obtained with UMAC over those obtained with SAC were about 25% and 15% higher for ibuprofen and ketoprofen, respectively. The application of the PVSDM 3D model evidenced that the ibuprofen molecule diffuses exclusively by surface diffusion and that the diffusion in the pore volume can be neglected. In addition, the simulated effluent treated with UMAC presented a removal percentage of 52% of the present compounds. These results show that the ultrasound technique has great potential to intensify the adsorption characteristics, generating a material with better features for ibuprofen and ketoprofen adsorption.